2021
DOI: 10.3390/machines9080158
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Nozzle Jet Flow in a Pelton Microturbine

Abstract: The characterization of flow through Pelton hydro turbines allows the optimization of their operation and maximization of energy performance. The flow in the injector of Pelton turbines and in the free jet area (the area from the injector outlet surface to the runner bucket inlet surface) is influenced by several parameters: the geometry of injector components (nozzle and injector spear), the injector opening, and the turbine head. The parameters of the free jet flow (velocity distribution, pressure distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Aplikasi kincir air adalah dengan meningkatkan kecepatan aliran air melalui nozzle, sehingga dapat meningkatkan effisiensi ekstraksi energi air (Du et al, 2020) (Haidar et al, 2012). Berbeda dengan model turbin aksial dan hydrokinetic, kecepatan aliran air disebabkan oleh draft tube pada konstruksi instalasinya (Nedelcu et al, 2021)(Niebuhr et al, 2019. Walaupun demikian konstruksi desain kincir air ini dapat mengurangi gesekan pada putaran turbin yang disebabkan oleh viskositas air.…”
Section: Gambar 2 Diskusi Terfokus Dalam Pengabdian Jurusan Teknik Mesinunclassified
“…Aplikasi kincir air adalah dengan meningkatkan kecepatan aliran air melalui nozzle, sehingga dapat meningkatkan effisiensi ekstraksi energi air (Du et al, 2020) (Haidar et al, 2012). Berbeda dengan model turbin aksial dan hydrokinetic, kecepatan aliran air disebabkan oleh draft tube pada konstruksi instalasinya (Nedelcu et al, 2021)(Niebuhr et al, 2019. Walaupun demikian konstruksi desain kincir air ini dapat mengurangi gesekan pada putaran turbin yang disebabkan oleh viskositas air.…”
Section: Gambar 2 Diskusi Terfokus Dalam Pengabdian Jurusan Teknik Mesinunclassified
“…Jung et al [17] found that pressure deviation caused by jet eccentricity and jet velocity imbalance are the main causes of jet diffusion. Nedelcu et al [18] found that the largest effect on flow variation is the head, followed by the opening and the nozzle diameter. Alimirzazadeh et al [19] simulated the interaction between two adjacent jets under eight operating conditions based on the finite volume particle method and found that jet perturbations produce load fluctuations and may exacerbate fatigue at speeds below and above the optimum efficiency point.…”
Section: Introductionmentioning
confidence: 99%
“…As the executing element of a high-pressure water jet system, the nozzle converts the pressure energy of the water into the kinetic energy of the water jet, and shoots out in the form of a high-speed water jet to break and punch the coal; therefore, the nozzle is one of the core components of the entire system. In recent years, local and international scholars have conducted substantial research on the structural parameters and working conditions of coal breaking and punching nozzle that affect water jet performance [7][8][9][10]. Wen et al [11] conducted a theoretical analysis and numerical simulation of computational fluid dynamics (CFD) to study the water jet performance of nozzles, particularly conestraight nozzles, with different flow channel shapes.…”
Section: Introductionmentioning
confidence: 99%